In-situ coated modified phosphate positive electrode material as well as preparation method and application thereof
By embedding LiB3H8 in situ on the surface of lithium iron phosphate material and performing synchronous in-situ sintering, the problems of low ion diffusion rate of lithium iron phosphate material and easy coating material are solved, which significantly improves the rate performance and cycle retention rate of the battery.
Patent Information
- Application Number
- CN202411609227.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-11
AI Technical Summary
The low ion diffusion rate of existing lithium iron phosphate materials and the easy coating material to fall off, resulting in poor cyclic retention, specific capacity and rate performance of the battery.
The preparation method of in-situ coated modified phosphate positive electrode material is adopted. By synchronously embedding LiB3H8 on the surface of lithium iron phosphate material, its three-dimensional lithium ion diffusion path is used to increase the diffusion rate of lithium ions, and synchronous in-situ sintering is used to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make it easier to make The cladding layer is closely linked to the surface of lithium iron phosphate.
It significantly improves the diffusion rate of lithium ions and the rate performance of the battery, improves the cycle retention rate and capacity, and avoids interface separation problems.
Smart Images

Figure CN119409158A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to an in-situ coated modified phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Compared with liquid batteries, solid-state batteries have higher safety, energy density and cycle life. The positive electrode materials of commercial solid-state lithium-ion batteries are mainly phosphate materials and ternary materials, and each has its own advantages and disadvantages. Among them, ternary materials can be used to extract and embed more lithium ions, have high energy density and good cycle performance, but because they contain precious elements such as Ni and Co, the preparation cost of ternary materials is relatively high, and Co is also toxic; while phosphate materials have a stable crystal structure, good cycle performance and safety, and because they do not contain precious elements such as Ni and Co, the raw material price is low. Although the energy density is low, it is more competitive in terms of cost.
[0003] Lithium iron phosphate (LiFePO4), as a representative of phosphate positive electrode materials, is widely known and widely used. From the perspective of the lithium iron phosphate unit cell structure, oxygen is arranged in a hexagonal close-packed arrangement, which creates diffusion resistance for lithium ions, resulting in a shortcoming in the application of LiFePO4 batteries at low temperatures and high performance; on the other hand, the FeO6 octahedron is separated by the PO4 tetrahedron, which affects the transmission of electrons. Regardless of the surface or the bulk phase, lithium ions present a one-dimensional diffusion path and a low lithium ion diffusion coefficient, resulting in various electrochemical properties of the battery, which greatly hinders the application of lithium iron phosphate materials in the field of solid-state batteries. In addition, the existing sintering coating modification method also has the problem that the coating material cannot be tightly combined with the positive electrode material, and it is very easy to fall off during use, which will also affect the battery's electrochemical properties such as cycle retention rate, capacity and rate. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the existing lithium iron phosphate material, such as low ion diffusion rate and easy detachment of the coating material, which leads to poor cycle retention rate, specific capacity and rate performance of the battery, thereby providing an in-situ coated modified phosphate positive electrode material and its preparation method and application for solving the above problems.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A preparation method of an in-situ coated modified phosphate positive electrode material comprises: weighing a lithium source and iron phosphate according to the stoichiometric ratio of lithium iron phosphate, adding a carbon source and a solvent for mixing, drying, and pre-sintering to obtain a sintered material; mixing the sintered material with nano boron powder and nano lithium powder under the protection of an inert atmosphere, and sintering in a reducing atmosphere to obtain the sintered material; wherein the molar ratio of the nano boron powder to the nano lithium powder is 3:1.
[0007] Preferably, the mass ratio of the nano boron powder to the sintered material is (3.24-32.4):1577.57.
[0008] Preferably, the sintering temperature is 600-700°C, preferably 650°C;
[0009] And / or, the sintering treatment time is 8-12 hours, preferably 10 hours;
[0010] And / or, the reducing atmosphere is hydrogen.
[0011] Preferably, the lithium source is lithium carbonate;
[0012] And / or, the carbon source is at least one of glucose and sucrose;
[0013] And / or, the solvent is water.
[0014] Preferably, the molar ratio of the carbon source to iron phosphate is (0.2-2.0):10;
[0015] And / or, based on the molar amount of iron phosphate being 10 mol, the amount of the solvent used is 400-600 g, preferably 500 g.
[0016] Preferably, the drying process is spray drying.
[0017] Preferably, the inlet temperature of the spray drying is 160-200°C;
[0018] And / or, the outlet temperature of the spray drying is 90-140°C;
[0019] And / or, the processing atmosphere of the spray drying is an inert atmosphere.
[0020] Preferably, the temperature of the pre-sintering treatment is 400-500°C;
[0021] And / or, the duration of the pre-sintering treatment is 1-4 hours;
[0022] And / or, the atmosphere of the pre-sintering treatment is an inert atmosphere.
[0023] The present invention also provides an in-situ coated modified phosphate positive electrode material, which is prepared by the above-mentioned method for preparing the in-situ coated modified phosphate positive electrode material.
[0024] The present invention also provides the use of the above-mentioned in-situ coated modified phosphate positive electrode material in a solid-state lithium ion battery.
[0025] In the present invention, the inert atmosphere is selected from nitrogen and / or argon.
[0026] The technical solution of the present invention has the following advantages:
[0027] A preparation method of an in-situ coated modified phosphate positive electrode material, comprising: weighing a lithium source and iron phosphate according to the stoichiometric ratio of lithium iron phosphate, adding a carbon source and a solvent for mixing, drying, and pre-sintering to obtain a sintered material; mixing the sintered material with nano boron powder and nano lithium powder under the protection of an inert atmosphere, and sintering in a reducing atmosphere to obtain the material; wherein the molar ratio of the nano boron powder to the nano lithium powder is 3:1. In order to solve the technical problem of low ion diffusion rate of lithium iron phosphate materials, the present invention proposes a technical concept of using LiB3H8 (a solid electrolyte with a three-dimensional lithium ion diffusion path) to perform surface in-situ embedded coating modification, that is, in the process of preparing lithium iron phosphate, the surface is simultaneously in-situ embedded and coated with LiB3H8, and the lithium ion diffusion path of LiB3H8 is used to improve the ability of lithium ions to enter the solid electrolyte after being deintercalated from the surface of lithium iron phosphate, and LiB3H8 is used as a lithium ion diffusion bridge between lithium iron phosphate and the solid electrolyte to improve the diffusion rate of lithium ions from lithium iron phosphate to the solid electrolyte, so that the rate performance of the battery material is significantly improved. At the same time, in order to prevent the solid electrolyte coating from phase separation with the lithium iron phosphate surface, simultaneous in-situ sintering is carried out, so that the coating is in solid-solid fusion contact with the lithium iron phosphate surface during the synthesis process. The contact surface is tight and firm, and the lithium ion migration transition is smoother. At the same time, the volume change and lattice distortion after the material releases lithium ions lead to increased particle stress during the cycle process. The in-situ generated strong interface is not prone to interface separation, which will not lead to the common problem of lithium ions being unable to diffuse after interface separation in solid-state lithium-ion batteries. The rate performance of the battery material is significantly improved, and it shows good cycle retention rate and capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1This is a SEM morphology image of the in-situ coated modified phosphate cathode material prepared in Example 1 of the present invention;
[0030] Figure 2 This is a SEM morphology image of the positive electrode material prepared in Comparative Example 1 of the present invention;
[0031] Figure 3 It is a cycle test chart of Examples 1-3 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0032] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0034] Example 1
[0035] This embodiment provides a method for preparing an in-situ coated modified phosphate positive electrode material, and the specific steps are as follows:
[0036] 1) Weigh 5 mol Li2CO3, 10.0 mol FePO4, 2 mol glucose and 500 g pure water, add them into a planetary ball mill for ball milling and mix them evenly, pump them into a spray drying device with an inlet temperature of 180°C and an outlet temperature of 100°C, spray dry them under a N2 atmosphere, place them under a nitrogen atmosphere, heat them to 450°C and keep them for 2 hours, cool them with the furnace, and obtain a burnt material;
[0037] 2) Weigh 1577.57g of the sintered material in step 1), 19.458g of nano boron powder, and 4.1646g of nano lithium powder, mix them evenly in a nitrogen atmosphere, then place them in a hydrogen atmosphere, heat them to 650°C and keep them for 10 hours, cool them with the furnace, crush them and pass them through a 325-mesh sieve to obtain a lithium iron phosphate positive electrode material for a solid-state battery, whose SEM morphology is as follows: Figure 1 In step 2), an experimental group without adding a sintering material (i.e., only adding 19.458g of nano boron powder and 4.1646g of nano lithium powder and mixing them evenly) was also set up and elemental analysis was performed on the materials prepared in the experimental group. The test results are shown in Table 1.
[0038] Table 1
[0039]
[0040] As shown in Table 1, the molar ratio of the synthesized solid electrolyte is Li:B:H=1:2.90:7.73.
[0041] Taking into account the instrument testing error, a solid electrolyte material was synthesized, close to LiB3H8.
[0042] Example 2
[0043] This embodiment provides a method for preparing an in-situ coated modified phosphate positive electrode material, and the specific steps are as follows:
[0044] 1) Weigh 5 mol Li2CO3, 10.0 mol FePO4, 0.2 mol glucose and 500 g pure water, add them into a planetary ball mill for ball milling and mix them evenly, pump them into a spray drying device with an inlet temperature of 160°C and an outlet temperature of 90°C, spray dry them under a N2 atmosphere, place them under a nitrogen atmosphere, heat them to 400°C and keep them for 4 hours, cool them with the furnace, and obtain a burnt material;
[0045] 2) Weigh 1577.57 g of the sintered material in step 1), 32.4 g of nano-boron powder, and 6.9346 g of nano-lithium powder, mix them evenly under a nitrogen atmosphere, then place them under a hydrogen atmosphere, heat them to 650° C. and keep them for 10 hours, cool them with the furnace, crush them and pass them through a 325-mesh sieve to obtain a lithium iron phosphate positive electrode material for a solid-state battery.
[0046] Example 3
[0047] This embodiment provides a method for preparing an in-situ coated modified phosphate positive electrode material, and the specific steps are as follows:
[0048] 1) Weigh 5 mol Li2CO3, 10.0 mol FePO4, 2 mol sucrose and 500 g pure water, add them into a planetary ball mill for ball milling and mix them evenly, pump them into a spray drying device with an inlet temperature of 200°C and an outlet temperature of 140°C, spray dry them under a N2 atmosphere, place them under a nitrogen atmosphere, heat them to 500°C for insulation treatment for 1 hour, cool them with the furnace, and obtain a burnt material;
[0049] 2) Weigh 1577.57 g of the sintered material in step 1), 3.24 g of nano-boron powder, and 0.6935 g of nano-lithium powder, mix them evenly under a nitrogen atmosphere, then place them under a hydrogen atmosphere, heat them to 650° C. and keep them for 10 hours, cool them with the furnace, crush them and pass them through a 325-mesh sieve to obtain a lithium iron phosphate positive electrode material for a solid-state battery.
[0050] Comparative Example 1
[0051] This comparative example provides a method for preparing an in-situ coated modified phosphate positive electrode material, and the specific steps are as follows:
[0052] 1) Weigh 5 mol Li2CO3, 10.0 mol FePO4, 2 mol glucose and 500 g pure water, add them into a planetary ball mill for ball milling and mix them evenly, pump them into a spray drying device with an inlet temperature of 180°C and an outlet temperature of 100°C, spray dry them under a N2 atmosphere, place them under a nitrogen atmosphere, heat them to 450°C and keep them for 2 hours, cool them with the furnace, and obtain a burnt material;
[0053] 2) The sintered material in step 1) is placed in a hydrogen atmosphere, heated to 650°C and kept for 10 hours, cooled with the furnace, crushed and sieved through a 325-mesh sieve to obtain a lithium iron phosphate positive electrode material for a solid-state battery, the SEM morphology of which is as follows: Figure 2 shown.
[0054] Comparative Example 2
[0055] This comparative example provides a method for preparing an in-situ coated modified phosphate positive electrode material, and the specific steps are as follows:
[0056] 1) Weigh 5 mol Li2CO3, 10.0 mol FePO4, 2 mol glucose and 500 g pure water, add them into a planetary ball mill for ball milling and mix them evenly, pump them into a spray drying device with an inlet temperature of 180°C and an outlet temperature of 100°C, spray dry them under a N2 atmosphere, place them under a nitrogen atmosphere, heat them to 450°C and keep them for 2 hours, cool them with the furnace, and obtain a burnt material;
[0057] 2) Weigh 1577.57 g of the sintered material in step 1), 0.1 mol of lithium hydride and 0.1 mol of nano-boron powder, mix them evenly under a nitrogen atmosphere, then put them into a reactor and fill them with hydrogen at a pressure of 30 MPa, keep them at 500° C. for 10 h, cool them with the furnace, crush them and pass them through a 325-mesh sieve to obtain a lithium iron phosphate positive electrode material for a solid-state battery.
[0058] Test Example 1
[0059] The electrochemical performance test was conducted on the lithium iron phosphate positive electrode material for solid-state batteries prepared in the above embodiments and comparative examples. The electrochemical performance test steps are as follows: weigh the lithium iron phosphate positive electrode material for solid-state batteries, carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, add solvent N-methylpyrrolidone (NMP) in a solid-liquid ratio of 2:1 to prepare positive electrode slurry, evenly coat the slurry on aluminum foil, bake at 105°C for 2h, cut the baked electrode sheet and put it into a tablet press for compaction (compacted density is 2.3g / cm 3), cut out small discs, assemble them in a nitrogen atmosphere, where the water and oxygen content is less than 0.1ppm, put the small discs into the positive side of the buckle battery shell, with the coated side facing the positive electrode, and add polyacrylonitrile (PAN) + Li7La3Zr2O 12 (LLZO) (the mass ratio of PAN:LLZO is 1:9), and then put in the negative electrode sheet (pure lithium sheet), gasket, spring, buckle the negative electrode shell, and package it into a CR2032 button battery. Among them, the charge and discharge system: the charging cut-off voltage is 4.3V, the discharge cut-off voltage is 3.0V; the first cycle is 0.1C charging, 0.1C discharging; the second cycle is 0.5C charging, 0.5C discharging; the third cycle is 1.0C charging, 1.0C discharging; then 1C charging and 1C discharging cycles 500 times to test the cycle retention rate (such as Figure 3 The test results are shown in Table 2.
[0060] Table 2
[0061]
[0062] As can be seen from Table 2, the 0.1C discharge specific capacity of the in-situ coated modified phosphate positive electrode material prepared by the present invention is greater than or equal to 166.5 mAh / g, the 0.5C discharge specific capacity is greater than or equal to 159.8 mAh / g, the 1C discharge specific capacity is greater than or equal to 153.0 mAh / g, and the 500 cycle performance is greater than or equal to 94.58%.
[0063] By comparing Example 1 with Comparative Example 1, it can be seen that the lithium iron phosphate coated solid electrolyte of this embodiment is applied to the solid-state battery. Since the positive electrode material is coated with the solid electrolyte in situ, it has good contact with the electrolyte in the solid-state battery. After the lithium ions escape from the lithium iron phosphate positive electrode body, they pass through the three-dimensional path of the solid electrolyte coated on the surface and smoothly enter the electrolyte of the solid-state battery. Therefore, the material has high capacity and good cycle performance. In Comparative Example 1, the LiB3H8 material is not coated in situ, and the lithium iron phosphate positive electrode material is in direct contact with the solid electrolyte in the solid-state battery. The performance difference between the two-phase interface is large and the two-phase interface is not tight enough. The conduction rate of lithium ions at the two-phase interface is low, and the performance of the material is poor.
[0064] By comparing Example 1 and Comparative Example 2, it can be seen that after the LiBH4 material synthesized by the raw material molar ratio in Comparative Example 2 is coated, the weak ion conductivity of the coated LiBH4 hinders the lithium ions from entering the electrolyte of the battery, which also leads to a decrease in capacity and cycle.
[0065] Depend on Figure 1 and Figure 2 By comparison, it can be seen that in the positive electrode material prepared in Example 1, the solid electrolyte LiB3H8 is tightly coated on the surface of the lithium iron phosphate material.
[0066] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing an in-situ coated modified phosphate positive electrode material, characterized in that: include: According to the stoichiometric ratio of lithium iron phosphate, a lithium source and iron phosphate are weighed, and a carbon source and a solvent are added to mix, dry, and pre-sinter to obtain a sintered material; The sintered material is mixed with nano boron powder and nano lithium powder under the protection of an inert atmosphere, and then placed in a reducing atmosphere for sintering to obtain the sintered material; wherein the molar ratio of the nano boron powder to the nano lithium powder is 3:
1.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the nano boron powder to the sintered material is (3.24-32.4):1577.
57.
3. The preparation method according to claim 1 or 2, characterized in that: The sintering temperature is 600-700°C, preferably 650°C; And / or, the sintering treatment time is 8-12 hours, preferably 10 hours; And / or, the reducing atmosphere is hydrogen.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The lithium source is lithium carbonate; And / or, the carbon source is at least one of glucose and sucrose; And / or, the solvent is water.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of the carbon source to the iron phosphate is (0.2-2.0):10; And / or, based on the molar amount of iron phosphate being 10 mol, the amount of the solvent used is 400-600 g, preferably 500 g.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The drying process is spray drying.
7. The preparation method according to claim 6, characterized in that: The inlet temperature of the spray drying is 160-200°C; And / or, the outlet temperature of the spray drying is 90-140°C; And / or, the processing atmosphere of the spray drying is an inert atmosphere.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The temperature of the pre-sintering treatment is 400-500°C; And / or, the duration of the pre-sintering treatment is 1-4 hours; And / or, the atmosphere of the pre-sintering treatment is an inert atmosphere.
9. An in-situ coated modified phosphate positive electrode material, characterized in that: The cathode material is prepared by the method for preparing the in-situ coated modified phosphate cathode material according to any one of claims 1 to 8.
10. Use of the in-situ coated modified phosphate cathode material according to claim 9 in a solid-state lithium-ion battery.